Antibiotik Profilaksis Pada Penyakit Jantung - Musa Ghufron; Muhammad Perdana Airlangga (Universitas Muhammadiyah Semarang, 2019)
Prophylactic Antibiotics in Heart DiseaseInfective endocarditis (IE) is an uncommon but lifethreatening infection. Despite advances in diagnosis, antimicrobial therapy, surgical techniques, and management of complications, patients with IE still have high morbidity and mortality rates related to this condition. Since the last American Heart Association (AHA) publication on prevention of IE in 1997, many authorities and societies, as well as the conclusions of published studies, have questioned the efficacy of antimicrobial prophylaxis to prevent IE in patients who undergo a dental, gastrointestinal (GI), or genitourinary (GU) tract procedure and have suggested that guidelines should be revised